Front Cover: Aminotenuazonic Acid: Isolation, Structure Elucidation, Total Synthesis and Herbicidal Activity of a New Tetramic Acid from Fruiting Bodies of Laccaria Species (Chem. Eur. J. 44/2019). Issue 44 (19th July 2019) - Schrey, Hedda; Backenköhler, Jana; Kogler, Herbert; Plaumann, Markus; Spiteller, Peter
Abstract : Is it recommended to consume the fruiting bodies of Laccaria bicolor? On the cover picture, the experiments leading to the detection of the so far unknown mycotoxin (5 S, 6 S )‐aminotenuazonic acid–structurally closely related to the well‐known tenuazonic acid–are shown in a cryptic way and some light is shed on the chemical secrets of Laccaria species. By a combination of analytical, chemical, and biological methods, the structure of aminotenuazonic acid was elucidated, a hypothetical biosynthesis was proposed, a total synthesis was developed, and its bioactivity was evaluated. More information can be found in the Full Paper by P. Spiteller, et al. on page 10333 .